Metodologias intervencionistas na perspectiva da teoria da atividade histórico-cultural: um aporte metodológico para estudos organizacionais - Cassandre, Marcio Pascoal (2012)
Coming from the premise of having the interventionist methodologies, originated from the Cultural Historical Activity Theory perspective, as recent part of qualitative researches in Administration in Brazil, they are theoretical-methodological proposals which must be put into reflection regarding the political, economic, social and institutional contexts of organizations that make use of it, to analyze the contradictions and the quest for development in productive activities. Comprehending such activities as a historical, complex, concrete, in movement and dialect phenomenon. Regarding such assertive, this paper is presented as a historical narrative of an expansive learning process. The historical course observed utilized as tools the self-confrontation method and the Change Laboratory®. The first empirical experience making use of the self-confrontation tool was made with food manipulators integrated to a school organization collective, based on the methodological strategy of the Clinic of Activity, developed by Yves Clot. The second experience supported by the self-confrontation method had as its basis a case study with an entrepreneur acting on the beauty care business. The third empirical experience occurred together to the Center for Research on Activity, Development and Learning (CRADLE), University of Helsinki. From the experiences, it can be considered that the interventionist methodologies analyzed are action and knowledge production methods, capable of generating conditions to the dialog of the individual with the action itself, the history, the activity system in which is bounded to and with the other subjects involved, directly or indirectly. At last, it was possible to comprehend that the practitioners of such methodologies are seen as individuals full of possibilities of development. With the learning process as a system of collective action, the respective practitioners, when assuming a common objective, reflect together the contrition of the concrete reality, and regarding their own tools and comprehensions, produce a new activity.